2016
DOI: 10.1128/aem.03437-15
|View full text |Cite
|
Sign up to set email alerts
|

Land Spreading of Wastewaters from the Fruit-Packaging Industry and Potential Effects on Soil Microbes: Effects of the Antioxidant Ethoxyquin and Its Metabolites on Ammonia Oxidizers

Abstract: c Thiabendazole (TBZ), imazalil (IMZ), ortho-phenylphenol (OPP), diphenylamine (DPA), and ethoxyquin (EQ) are used in fruitpackaging plants (FPP) with the stipulation that wastewaters produced by their application would be depurated on site. However, no such treatment systems are currently in place, leading FPP to dispose of their effluents in agricultural land. We investigated the dissipation of those pesticides and their impact on soil microbes known to have a key role on ecosystem functioning. OPP and DPA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
8
18
1
Order By: Relevance
“…Considering that in the cultures inhibited by EQ (i) EQNL was formed at concentrations substantially lower than those expected to result in an inhibitory effect on the AO tested, and (ii) QI was formed at concentrations equal or higher than those expected to induce an inhibitory effect on the AO tested, we suggest that QI is the main determinant of the persistent inhibitory effect of EQ on AO and NOB. This is consistent with our previous soil studies where EQ, but mostly QI when applied alone, induced a significant inhibition of potential nitrification and transcription of both bacterial and archaeal amoA genes (32). Unlike our previous soil studies where QI showed equivalent inhibitory effects against AOB and AOA, we observed a difference in the inhibition potential of QI between these two AO groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Considering that in the cultures inhibited by EQ (i) EQNL was formed at concentrations substantially lower than those expected to result in an inhibitory effect on the AO tested, and (ii) QI was formed at concentrations equal or higher than those expected to induce an inhibitory effect on the AO tested, we suggest that QI is the main determinant of the persistent inhibitory effect of EQ on AO and NOB. This is consistent with our previous soil studies where EQ, but mostly QI when applied alone, induced a significant inhibition of potential nitrification and transcription of both bacterial and archaeal amoA genes (32). Unlike our previous soil studies where QI showed equivalent inhibitory effects against AOB and AOA, we observed a difference in the inhibition potential of QI between these two AO groups.…”
Section: Discussionsupporting
confidence: 93%
“…animals, plants, and soils) (46). In this study, EQ was rapidly transformed to QI and EQNL, with the former being the major but least persistent transformation product, while the latter being a minor but more persistent product, in line with previous studies in soil (32, 33). We observed a different inhibition potential for AOB and AOA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, Karas et al (9) demonstrated the major role of TPs of chlorpyrifos and isoproturon on the inhibition of soil microbial functions. Similarly, Papadopoulou et al (10) showed that quinone imine, the oxidized TP of ethoxyquin (an antioxidant used in the fruit-packaging industry) was equally as toxic as, or more toxic than, the parent compound to ammonia-oxidizing microorganisms (AOM). This group has been shown to be particularly sensitive to environmental perturbations (11) including pesticide exposure (6,9).…”
mentioning
confidence: 99%
“…NOEC fish = 12 μg L −1 ) [8]. We recently reported TBZ concentration levels in soils adjacent to fruit packaging plants of up to 12,000 mg kg −1 resulting in a depleted bacterial diversity [9]. The extensive environmental contamination by TBZ is the result of its high persistence (DT50 (soil - aerobic)> 365 days) [10] and the lack of implemented methods for the treatment of TBZ-contaminated agro-industrial effluents (despite the implementation of relevant EC legislation) [11].…”
Section: Introductionmentioning
confidence: 99%